Teologi Perempuan: Menyejajarkan Atau Menyatukan? - Saiful Amin (UIN Maulana Malik Ibrahim Malang, 2001)
Discussing social injustice against women with gender analysis, will often face opposition from both men and women themselves. This is because questioning the status of women is essentially concerned with established systems and structures. In addition there are many misunderstandings about why women's issues should be questioned. This paper discusses gender issues that essentially discuss power relationships that involve individuals. This paper is not meant to discuss feminist flows, but rather addressing the debate about gender in the theological discourse of Islamic intellectual traditions. In the discourse of women's theology in Islam, its social implications will be colored by the tug of war between the struggle to equalize gender on the one hand and the struggle to unite them in cosmic harmony on the other. The first seeks to eliminate the social injustice that affects women by raising the existence of gender in order to be equal and equal. While the latter seeks to eliminate social injustice by reinforcing, not to elevate gender differences in order to mutual respect and equality in the natural unity. Membincang ketidakadilan sosial terhadap perempuan dengan analisis gender, sering kali akan menghadapi perlawanan baik dari kalangan kaum laki-laki maupun perempuan sendiri. Ini disebabkan karena mempertanyakan status perempuan pada dasarnya adalah mempersoalkan sistem dan struktur yang sudah mapan. Selain itu banyak terjadi kesalahpahaman tentang mengapa masalah kaum perempuan harus dipertanyakan. Tulisan ini mendiskusikan persoalan gender yang pada dasarnya membahas hubungan kekuasaan yang melibatkan individu. Tulisan ini tidak dimaksudkan untuk mendiskusikan tentang aliran-aliran feminisme, tetapi lebih ditujukan pada perdebatan tentang gender dalam wacana teologis tradisi intelektual Islam. Pada wacana teologi perempuan dalam Islam, implikasi sosialnya akan diwarnai oleh tarik ulur antara perjuangan menyetarakan gender di satu sisi dan perjuangan menyatukan keduanya dalam keharmonian kosmis di sisi yang lain. Yang pertama berusaha menghilangkan ketidakadilan sosial yang menimpa perempuan dengan mengangkat eksistensi gender agar bisa sama dan setara. Sedangkan yang kedua berusaha menghilangkan ketidakadilan sosial itu dengan mempertegas, untuk tidak mengangkat perbedaan gender agar bisa saling menghormati dan melengkapi dalam kesatuan alamiah.